Applicability of Entry to Practice Examinations for Optometry in Canada - Woo, Stanley; Hrynchak, Patricia; Hutchings, Natalie (Canadian Journal of Optometry, 2022)
High-stakes assessment for entry-to-practice is a critical component for the optometric profession's regulatory bodies in carrying out their duties to assure safe, effective, and ethical practice by their respective registrants. In 2019, the College of Optometrists of Ontario approved the acceptance of the United States (US) entry-to-practice examination for optometry, the National Board Examiners in Optometry (NBEO®), as an acceptable alternative assessment for the Canadian entry-to-practice examination, the Optometry Examining Board of Canada (OEBC). This decision was not unanimously supported in stakeholder feedback. In this paper, the development and structure of the two assessments are described. A global consensus framework is applied to identify the appropriateness of the assessments for Canada, and a similar change in entry-to-practice for nursing is examined for contextual correlates. Although intrinsically satisfactory for their respective jurisdictions, the NBEO® does not appear to satisfy the critical criteria of validity and acceptability for Ontario or, more broadly, Canada. Cultural and systemic differences between the Canadian and US health systems were also identified as additional barriers. Lastly, major future vulnerabilities for the profession lie in the availability of the entry-to-practice examination to all Canadians, Anglophone and Francophone.